Optimal Control of the Instationary Three Dimensional Navier-Stokes-Voigt Equations. (2nd April 2016) - Anh, Cung The; Nguyet, Tran Minh
ABSTRACT: We study an optimal control problem with quadratic objective functional for the three dimensional Navier-Stokes-Voigt equations in bounded domains. We show the existence of optimal solutions, the necessary optimality conditions and the sufficient optimality conditions. The second-order optimality conditions obtained in the article seem to be optimal.